Seizure disorders and developmental disorders: impact on life of affected families : a structured interview - Spindler, Ulrike; Syrbe, Steffen (European journal of pediatrics, 2017)
Seizure disorder and developmental disorder are two of the most common chronic disorders in childhood. Data on perceived parental burden and specific effects on daily life is scarce. We performed a structured interview, consecutively talking to all parents of pediatric outpatients of our university hospital diagnosed with seizure or developmental disorder. Three hundred seven parents (of 317 affected children: 53 with seizure disorder, 44 with specific developmental disorder, 35 with learning disorder, 71 with intellectual disability, 15 with seizure + specific developmental disorder, 23 with seizure + learning disorder, 76 with seizure disorder + intellectual disability) were interviewed. Parents of children with both seizure disorder and intellectual disability stated the highest constraints in daily life, regarding friends, hobbies, emotional pressure, occupation, partnership, habitation, and financial burden. Due to diagnosis of seizure or developmental disorder, 155/307 (51%) parents reduced their working hours/stopped working, 62/307 (20%) changed their habitation, and 46/307 (15%) broke up. As judged by parents, 148/317 (47%) children are being discriminated against, even own family/friends and educators are held responsible. Conclusion: Parents perceive changes in their daily life and discrimination of their children due to their children’s seizure and developmental disorders. An intellectual disability combined with seizure disorder caused the highest constraint.